Comparison of academic outcomes of epidemiology and biostatistics course between traditional lecture and flipped classroom blended approach in 2 nd year medical students: A retrospective cohort study - On anong Binsomprasong (2020)
© 2019 Siriraj Medical Journal. Objective: To compare academic outcomes between integrated flipped classroom (FC) and solely traditional lecture (TL) teaching approach among 2 nd year medical students in Epidemiology and Biostatistics course. Methods: General information and academic achievements including grade point average, scores of the basic statistics course and scores of Epidemiology and Biostatistics course were extracted from the database of the Education Department. The records were excluded if they belonged to repeated or transferred students. The students in 2014 and 2015 academic year represented the TL group and the FC group respectively. The main outcome was the examination score from the two groups which was converted to a comparable scale out of a hundred. Results: Six-hundred twenty-eight records were included in the analysis. Based on independent t-test, the TL group showed higher mean score as compared to the FC group (p-value < 0.01). Further comparison using ANCOVA adjusted for age, gender, hometown location, high school location, grade point average and score of a basic statistics course showed a higher score in the TL group (p-value < 0.01). Conclusion: TL yielded higher examination score than FC from this retrospective study.